Função pulmonar dos pacientes com fibrose cística colonizados por Pseudomonas aeruginosa no Pará - FALCÃO, Edilene do Socorro Nascimento (Universidade Federal do Pará, 2013)
Pseudomonas aeruginosa is an opportunistic pathogen in cystic fibrosis becoming the most frequent cause of lung infection; it is responsible for high mortality rates in patients who present this disease. The goal of this study is to showing spirometric and clinic characteristics of patients who present cystic fibrosis and who are attended at João de Barros Barreto University Hospital (HUJBB), in the State of Pará. A retrospective study was performed with 44 patients´ notes record who were attended at HUJBB during the 1997 to 2007 time frame; these patients fit into inclusion criteria, in which 14 presented P. aeruginosa bacteria colony, nine patients died. The significance rate presented was of 5%. Within the group who was colonized by P. aeruginosa, ten patients were women and the median age for their initial symptoms was of 0.3 ± 0.6 year which was significantly different when compared with patients who didn´t present the bacteria colony (p<0.05). The median age for diagnosis was of 13.1 ± 10.8 in colonized patients and all of them presented respiratory symptoms pertaining to the diagnosis. The median of the predicted percentage values of spirometries for initial and final evaluation of the colonized group was VEF1 (60.0 ± 25.0%) and (47,82 ± 16.1%) and FEF25-75% (42.5 ± 22.9%) and (26.5 ± 17.9%), and in the non-colonized group, the median was VEF1 (79.2 ± 21.0%) and (79,6 ± 18.0%) and FEF25-75% (69.2 ± 26.7%) and (68.9 ± 26.8%), respectively (p<0.005). The median initial Shwachman score in the colonized patients was 42.9 ± 13.5 and in the non-colonized patients it was 68.4 ± 15.1 (p<0.0001), and at the final evaluation the median was 36.6 ± 18.7 and 73.6 ± 12.3 (p<0.0001), respectively, showing important difference between the two groups. Factors related to deaths found in the study were related to P. aeruginosa colonization, inadequate nutritional status and reduced VEF1. In the studied casuistry, a larger damage to respiratory function and older median age for diagnosis were found in the State of Pará when compared to other Brazilian States. These data reinforce the need for action towards precocious diagnosis in the State of Pará so that an efficient and guided therapeutic approach is put into practice guiding to survival increase and quality of life improvement for these individuals, which is the main goal of professionals involved in the assistance practice area.